A DESCRIPTIVE ANALYSIS OF NORTH CYPRUS TOURISM - AKIS, S; WARNER, J (Butterworth-Heinemann Ltd, 1994)
Tourism is the main provider of foreign exchange for the Turkish sector of Cyprus and, as such, it is important for the Turkish Cypriots to keep their visitors happy. This paper reports the findings of a survey of the attitudes of both holiday-makers and suppliers of tourism services to tourism in North Cyprus. As a consequence of the survey, suggestions are made for the diversification and further development of tourism.